2018
DOI: 10.14419/ijet.v7i2.17.11553
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ECG Arrhythmia for Heart Disease Detection using SVM and Cuckoo Search Optimized Neural Network

Abstract: This paper tried to address several topics concerning the analysis, synthesis and compression of the electrocardiogram signal (ECG) using the MIT database. We detect the R-wave by identifying the location of each interval delineating a QRS complex using unbiased and biased estimators. In the second part of the work, we segmented the signal into RR periods constituting the vectors of a data matrix, where we extracted its main components in order to reduce the size of the cardiac information, and then further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As previously indicated, there were several inconsistencies in terms of assessment measures published by the literature. For example, some research reported their results with accuracy [ 45 ]; others provided with accuracy, precision, recall, and F1-score [ 42 ]; while a few studies emphasized sensitivity, specificity, and true positive [ 67 ]. As a result, there were no criteria for the authors to follow in order to report their findings correctly and genuinely.…”
Section: Discussionmentioning
confidence: 99%
“…As previously indicated, there were several inconsistencies in terms of assessment measures published by the literature. For example, some research reported their results with accuracy [ 45 ]; others provided with accuracy, precision, recall, and F1-score [ 42 ]; while a few studies emphasized sensitivity, specificity, and true positive [ 67 ]. As a result, there were no criteria for the authors to follow in order to report their findings correctly and genuinely.…”
Section: Discussionmentioning
confidence: 99%
“…Within this endeavour, the researchers harnessed the potential of machine learning approaches, including Support Vector Machine (SVM) and the ingenious Cuckoo Search-Optimized Neural Network. The results were impressive, with the support vector machine yielding an enhanced accuracy rate of 94.44% [18].…”
Section: Related Studiesmentioning
confidence: 99%
“…The results showed that the backpropagation neural network and Logistic Regression algorithms achieved an accuracy of 85.074% and 92.58%, respectively. The work in [129] encompasses two domains: signal processing and statistical learning. Leveraging signal processing techniques, authors have successfully segmented and represented each heartbeat through a vector of distinctive characteristics.…”
Section: Machine Learning Models For Cardiovascular Disease Predictio...mentioning
confidence: 99%